BRIDGING THE BUSINESS AND HUMAN RIGHTS DIVIDE WITH LESSONS FROM UNCLOS’ DEEP SEA MINING REGIME - Sipalla, Humphrey; Sainz-Borgo, Juan Carlos (KABARAK UNIVERSITY, 2016)
The norms that govern international economic law have for decades been criticised by the Third World for favouring the interests of western Industrialised Powers to the detriment of Third World peoples and their states. Among the contested issues is whether the very structure of international law facilitates this skewed situation, in matters such as accountability abeyances of business entities for human rights violations and the clash of state obligations under international human rights and international economic law. The United Nations Convention on the Law of the Sea (UNCLOS) regulates matters that undoubtedly affect critical economic interests of states. It is lauded for having, through tortured negotiations (1973-82, 90-94), arrived at far more equalising standards between established maritime powers and economically weaker Third World states. The UNCLOS deep sea mining regime was so contested that it delayed UNCLOS’ acceptance among established economic powers for over a decade. In this paper, we interrogate whether this regime offers a viable model that the business and human rights divide could emulate, both in terms of the viability of the ‘treaty road’ as well as establishing reasonable terms of assigning international responsibility among international organisations, states and corporate entities within municipal law, especially since the 2011 ITLOS Advisory Opinion on responsibilities and obligations of states, arose from concerns of small island states.
Keywords: Human Rights; Business; UNCLOS’ Deep Sea Mining